1987
DOI: 10.1055/s-2007-998692
|View full text |Cite
|
Sign up to set email alerts
|

Änderungen des nasalen Volumsstromes nach lokaler Applikation des Neuropeptides Substanz-P und von Capsaicin

Abstract: Einfuhrung und Fragestellung Die terminate Strombahn des GefaIsystems der menschtichen Nasenschleimhaut ist morphotogisch hoch differenziert. Ihre feine Struktur aus Arterien, Arterioten, Kapillarsystemen, arteriovenösen Anastomosen, venösen Sinusoiden, Venolen und Venen ermoglichen es der menschlichen Nasenschteimhaut im Zusammenspiel mit den Ge-fäIsphinkteren rasch den Zustand der Blutfullung zu verändern, und so ihren physiplogischen Aufgaben wie Erwärmung und Befeuchtung, nachzukommen. Kontrottiert wird de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The present results with respect to blockage after SP stimulation of the nasal mucosa are in accordance with those of Wolf et al [8] and Devillier et al [9]. The presence of this symptom has to be regarded as a di rect action upon the vasculature (nasal sinusoids).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present results with respect to blockage after SP stimulation of the nasal mucosa are in accordance with those of Wolf et al [8] and Devillier et al [9]. The presence of this symptom has to be regarded as a di rect action upon the vasculature (nasal sinusoids).…”
Section: Discussionsupporting
confidence: 93%
“…Wolf et al [8] and Devillier et al [9] demonstrated an increase in nasal airway resistance, whereas others were un able to confirm this [10]. Similar results were seen for mucociliary activity and nasal secretion [II,12].…”
Section: Introductionmentioning
confidence: 70%
“…The present study shows that long‐term use of benzalkonium chloride nasal spray alone induces mucosal swelling. The nose has a reflex pathway consisting of afferent unmyelinated C fibers and efferent parasympathetic nerves, 22,23 and the activation of nonmyelinated C fibers induces nasal blockage 24 . Long‐term exposure to irritants may cause alterations in vasomotor tone with increased parasympathetic activity, which results in vascular dilatation, increased permeability, edema, and nasal blockage 25…”
Section: Discussionmentioning
confidence: 99%
“…nerves' an activatIOn 0 non-mye mate c-1 ers 10-duces nasal blockage. 22 Exposure to irritants may induce an alteration of the vasomotor tone with increased parasympathetic activity, which results in vascular dilation, increased penneability, edema, and nasal blockage?3 The mucosal instability may be due to that benzalkonium chloride is acting as an irritant.…”
Section: Discussionmentioning
confidence: 99%